Modulation of Stress Responses by FKBP5 In Zebrafish and Rainbow Trout - St-Amant, Donna (Université d'Ottawa / University of Ottawa, 2026)
Environmental challenges activate the hypothalamic-pituitary-interrenal (HPI) axis in fishes, increasing synthesis of the glucocorticoid stress hormone cortisol. Cortisol binds to the glucocorticoid receptor (GR), which activates negative feedback regulation of the HPI axis. In mammals, activation of GR increases FK506-binding protein 51 (FKBP5), a co-chaperone of GR that inhibits its activity. The present study hypothesized that FKBP5 and GR interactions similarly contribute to prolonged elevation of cortisol during chronic stress in rainbow trout (Oncorhynchus mykiss). Subordinate trout exhibited elevated plasma cortisol, and after 4 d of social interaction, also displayed elevated transcript abundance of fkbp5B. Treatment of subordinates with an FKBP5 inhibitor, SAFit2, tended to lower cortisol but the effects were not clear cut. The expression of fkbp5 in zebrafish (Danio rerio) was assessed during early development and in response to an acute stressor in both wildtype fish and those lacking the GR (GR-KO). The GR-KO fish exhibited significantly lower fkbp5 expression in both larvae and adults compared to wildtype fish. The transcript abundance of fkbp5 exhibited transient elevation in response to an acute stressor in wildtype fish. Overall, my findings suggest that FKBP5 plays a role in maintaining elevated cortisol during chronic stress in rainbow trout and show that GR regulates the baseline expression of fkbp5 across development in zebrafish.
Keywords: Stress; Cortisol; Zebrafish; Rainbow Trout; FKBP5; Stress Response; Chronic Stress